Seasonal Water Crises and Social Dilemmas in Semi-Arid Areas of the Lake Zone of Tanzania - Laizer, L. M; Gibson, R.W; Lukonge, E (International Journal of Asian Social Science, 2018)
The absence of formal institutions regulating water resources indicated a need to examine how informal governance works in semi-arid areas of the Lake Zone of Tanzania. Ostrom’s theory of common property resources was adapted to develop a questionnaire administered to 162 households using five different water sources (lake/dam, ponds near lake/dam, ponds, wells and waterholes) along with focus group discussions (6), key informant interviews (33) and field observations. The results indicated that communities do not have water management systems where water is abundant (lake/dam and ponds near these water sources). Conversely, where water is scarce (ponds, wells and water holes), communal water management occurs. However, such communal water governances are location specific and limited and, though they appear to function well at preventing water exhaustion, they fail to resolve the complex social dilemmas in that ecological system. Thus, most water resources are dominated by households with sound economic resource base, they take deliberate efforts to establish private wells in wetlands to intercept underground resources, raising issues of equity, contamination of underground water resources and human safety. Sandy river beds seemed to represent the worst ‘tragedy’ of unmanaged common resources, often being located in ‘no-man’s land’ between districts or regions, with uncontrolled competition resulting in enormous water holes dug by local resource users from both sides, and exhaustion by those with the deepest waterholes and access to engine-driven pumps. There are two water main crises: (1) too little is available to meet the current demand during an annual prolonged dry season (6-7 months) and (2) increasing social dilemmas on how to manage the little available. How external interventions could address these issues is discussed.